RETRACTED ARTICLE: THE CORRELATION OF LEARNING INDEPENDENCE ATTITUDES AND STUDENT’S LEARNING ACHIEVEMENT ON PHYSICS LEARNING BASED-PORTFOLIO - Saefullah, Asep; Siahaan, Parsaoran; Sari, Ika Mustika (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2017)
Abstract This study aimed to determine correlation between learning independence attitudes and student’s learning achievement. Type of this research is a correlation study to detect the connection of learning independence attitude’s variance in relation to learning achievement variance. This study used an attitude scale to measure the student’s learning independence attitude and objective multiple-choice questions to measure the student’s learning achievement. The results showed that there is a positive correlation (unidirectional) and significant betweenthe learning independence attitude and learning achievement. This means that the better student’s learning independence attitude, it will be the better students learning achievement. The attitude of learning independence contributed to 40.96% of students learning achievement. Keywords: Learning Independence Attitude, Learning Achievement.